Convergence tests of infinite series - 496875 Sakthiyavaani Balakrishnan; Che Lokman Jaafar; Fakulti Sains (2004)
Project Paper (Sarjana Muda Sains serta Pendidikan (Matematik)) - Universiti Teknologi Malaysia, 2004